The effect of individual and mixtures of mycotoxins and persistent organochloride pesticides on oestrogen receptor transcriptional activation using in vitro reporter gene assays. (August 2019) - Eze, Ukpai A.; Huntriss, John; Routledge, Michael N.; Gong, Yun Yun; Connolly, Lisa
Abstract: The mycotoxins zearalenone (ZEN) and alpha-zearalenone (α-ZOL), which are common contaminants of agri-food products, are known for their oestrogenic potential. In addition to mycotoxins, food may also contain pesticides with oestrogenic properties such as 1, 1, 1-trichloro-2, 2-bis(p-chlorophenyl) ethane ( p, p' -DDT) and 1, 1-dichloro-2, 2-bis( p -chlorophenyl) ethylene ( p, p' -DDE), raising the question on the potential effects of individual and combinations of these xeno-oestrogens on the action of natural oestrogens. The present study employed a mammalian reporter gene assay to assess the effects individual and binary combinations of these environmental and food-borne contaminants on oestrogen nuclear receptor (ER) transactivation. As expected, α-ZOL and ZEN exhibited the strongest oestrogenic potency (EC50 : 0.27 ± 0.121 nM and 1.32 ± 0.0956 nM, respectively) whereas p, p' -DDT and p, p' -DDE had weak ER agonistic activity with the maximal response of 28.70 ± 2.97% and 18.65 ± 1.77%, respectively. Concurrent treatment of the mycotoxins and/or pesticides, individually or in binary combination, with 17β-oestradiol (E2 ) showed either additive, synergistic or antagonistic interactive effects on E2 -mediated ER response, depending on the combination ratios, the concentration range of xeno-oestrogens, and the concentration of E2 . This study highlights the importance of assessing the mixture effects of chemical contaminants in risk assessment, especially in the area of reproductive and developmental toxicity. Highlights: The effects of individual and binary mixtures of mycotoxins and pesticides on oestrogen receptor (ER) transcription response was evaluated. Zearalenone (ZEN) and α-zearalenol (α-ZOL) exhibited the strong oestrogenic potency. ZEN or α-ZOL, alone or in combination, antagonised the ER response mediated by 10 nM of 17β-oestradiol (E2 ). Binary combination of ZEN or α-ZOL with either 1, 1, 1-trichloro-2, 2-bis( p -chlorophenyl) ethane ( p, p' -DDT) and 1, 1-dichloro-2, 2-bis( p -chlorophenyl) ethylene ( p, p' -DDE) antagonised the ER response mediated by E2 . Equimolar concentrations of p, p' -DDT and p, p' -DDE at 50 μM completely inhibited the ER response mediated by E2 .